Efektivitas Terapi Zikir dalam Mengurangi Kecemasan pada Remaja Menjelang Ujian - Syahdiah, Utami; Fadhliah, Mursyidatul; Nurhidayah, Nurhidayah; Sakni, Ahmad Soleh; Lutfiah, Winona (Jurnal Penelitian Ilmu Ushuluddin, 2022)
This study aims to discuss the effectiveness of dhikr therapy in reducing anxiety in adolescents. This study uses a quantitative approach with case methods and field research, while the instrument used is a questionnaire containing questions. The results of this study indicate that adolescents or students experience anxiety in facing exams and by doing dhikr therapy the heart becomes calm so that when they are about to take the exam they become focused and fluent. In conclusion, dhikr itself is a prayer which will remember and express feelings, desires and desires. So that with dhikr people will get peace of mind and inner relief, because they will remember themselves and feel reminded by Allah SWT.